Determination of the occlusal vertical dimension in edentulous patients using lateral cephalograms. (1st April 2018) - Enkling, N.; Enkling‐Scholl, J.; Albrecht, D.; Bornstein, M. M.; Schimmel, M.
Summary: The determination of the occlusal vertical dimension (OVD) in edentulous patients is based on clinical assessment with high variability. This study tested the hypothesis: The average OVD in edentulous patients with conventional dentures is too low compared to orthodontic norms, when only clinical parameters are used for the determination of the OVD. Edentulous patients with conventional full dentures were enrolled. Clinical parameters were judged by two senior prosthodontists. Digital lateral cephalograms were taken and served to calculate the OVD according to the lower face height angle (ANS‐Xi‐D) taking tooth‐independent facial growth patterns into account. The ANS‐Xi‐D angle was compared with reference values by applying one‐sample mean comparison tests. Thirty‐six participants (17 female, 19 male; mean age 65.3 ± 10.6 years) were enrolled in this study. Clinically, the OVD of four dentures was judged too low, in one case too high, and in the other 31 cases as correct. The mean ANS‐Xi‐D angle was 48.28°±4.86 and statistically not different to the norm value of 49°±4 (n.s.). There was a tendency that the ANS‐Xi‐D angle was different between participants with different tooth‐independent facial growth patterns (ANOVA, P = .0548). Predominantly, clinically sufficient prostheses show adequate ANS‐Xi‐D angles. Short‐face type denture patients are often restored to comply with mesiofacial norms. The determination of the OVD based on lateral cephalography is not recommendable to be a standard diagnostic parameter. Orthodontic norms are derived from dentate cohorts and might not take the continuing facial growth and other confounding factors of edentulous subjects into account.